ADVANCEMENTS IN THE CONSTRUCTION AND TECHNOLOGY OF POLYCOMPONENT KNITTED FABRICS FOR SEASONAL CLOTHING - Turdiyev, Maxmudjon; Xomidov, Abdumajid Abdurashid o‘g‘li; To‘rayev , Xusniddin Abdullajonovich (Educational Research in Universal Sciences, 2023)
This article explores the recent developments in the construction and technology used to create seasonal clothing made from polycomponent knitted fabrics. The article discusses the benefits of using polycomponent knitted fabrics, including their versatility, durability, and comfort. The article also covers the latest advancements in technology used to create these fabrics, such as computerized knitting machines and advanced dyeing techniques. Additionally, the article examines how these advancements have impacted the fashion industry and provided designers with new opportunities for creativity.